Communications Between Organizations and Their Markets in Emerging Economies: a Research Agenda - Schultz, Don E. (Organizations and Markets in Emerging Economies, 2010)
Most marketing, and particularly marketing communications concepts and approaches, have been developed and codified in western economies. Academicians and professionals have then tried to export those concepts to emerging markets, often with little success. In this paper, we argue many of those concepts are not applicable or relevant for the emerging economies around the world. Yet, due to the constrained and controlled nature of academic publishing, little new information has been developed or distributed on the differences and needs of scholars and professionals in emerging economies. This paper suggests a new marketing communications research agenda for emerging economies based on four specific areas: (1) consumers and consumer behaviors, (2) brands and branding, (3) communication content and context and (4) emerging communication delivery systems. The authors encourage editors of academic journals to recognize the need and be more open to emerging economy research and papers.
Keywords: marketing and marketing communications research; emerging economies; research agenda; western cultural biases in research; new media